The Far Ultraviolet Wavelength Dependence of the Lunar Phase Curve as Seen by LRO LAMP. Issue 10 (8th October 2018) - Liu, Y.; Retherford, K. D.; Greathouse, T. K.; Raut, U.; Mandt, K. E.; Hendrix, A. R.; Cahill, J. T. S.; Gladstone, G. R.; Grava, C.; Egan, A. F.; Kaufmann, D. E.; Pryor, W. R.
Abstract: We present detailed photometric properties of the Moon at far ultraviolet wavelengths. The far ultraviolet data from the Lunar Reconnaissance Orbiter (LRO) Lyman Alpha Mapping Project (LAMP) instrument were used to derive two Hapke photometric parameters, the single‐scattering albedo, w, and the asymmetry factor, b, in the single‐particle phase function, for selected mare and highland regions. The derived single‐scattering albedo spectra show blue slopes for both regions. Furthermore, the negative values of the asymmetry parameter, for both regions, indicate backscattering from the surface. The derived photometric parameters were used to normalize the observed reflectance and remove the photometric effects, resulting in significant improvement in the quality of the LAMP dayside maps. Plain Language Summary: The photometry of the Moon gives us much information about the optical properties (i.e., brightness and color) of lunar surface. Using the data from an instrument called Lyman Alpha Mapping Project onboard the Lunar Reconnaissance Orbiter, we studied the detailed photometric properties of the two regions (selected mare and highland regions) on the Moon at far ultraviolet wavelengths. We used an empirical model called Hapke model to describe the surface reflectance at far ultraviolet wavelengths and then used the model to fit the curves of the reflectance as a function of phase angle (angle between direction of incoming sunlight and the direction of reflected sunlight toward the observer). The fitting process gives the Hapke parameters, which can be used to correct the photometric effects on the data due to the varying viewing geometries. Our corrections result in significantly improved Lyman Alpha Mapping Project reflectance maps. Key Points: Phase curves at far ultraviolet wavelengths over selected mare and highlands regions of the Moon were investigated with LRO LAMP data Two Hapke photometric parameters, the single‐scattering albedo, w, and the asymmetry factor, b, were derived with a simplified Hapke model Photometric correction using the derived Hapke parameters has significantly improved the quality of the LAMP dayside maps